Riba Dalam Al-Quran Dan Strategi Menghadapinya - Ahmad Naufal (Prodi Perbankan Syariah FAI UMT, 2019)
The systemic practice of usury has caused the monetary sector to separate from the real sector, causing a prolonged economic downturn. This has actually been warned in the Qur'an. For this reason, this study aims to explore the